TiO2 thin Films for Biofouling Applications - Soethe,Viviane Lilian (2017)
This work presents a study of TiO2 thin films prepared by sputtering, for using as protection for biofouling action on marine structures. Titanium oxide thin films were prepared with different amount of oxygen on the surface of regular 1020 steel, a structural material for marine technology. The cristalline structure analysis evidenced the formation of anatase and rutile phases, as well as an amorphous phase of titanium oxide. Roughness measurements shown that the surface finish can contribute to the fixation of microorganisms. The crystalline TiO2 thin films was evaluated as a potential biofouling protective coating. Contact angle measurements revealed that under UV-C light, the material evidenced a changing in wettability from hydrophobic to hydrophilic behavior, what is associated to the activation of photocatalytic reactions that is nocive for living beings on its surface. The effect of marine ambient on sample corroborates this conclusion, where after 6 months of exposure it was not sufficient for growing of biofouling on surface.